Pengaruh Kesulitan Keuangan, Ukuran Perusahaan Klien dan Pergantian Manajemen Terhadap Auditor Switching - Ronituppal; Sophia Andini (UNIVERSITAS KALBIS, 2022)
This study aims to examine the effects of financial crisis, client firm size, and management turnover on auditor switching. The population of this study is comprised of manufacturing firms listed on the Indonesia Stock Exchange (IDX) between 2014 and 2018. 126 companies gave research samples using a method of purposive sampling, and 630 pieces of research data were collected. The method of data analysis employed is regression logistic analysis. The results demonstrated that the size of the client company and a change in management had negative and positive effects, respectively, on the voluntary auditor switching, whereas financial hardship has no effect.